Correlations between brain structures and study time at home in healthy children: a longitudinal analysis. Issue 6 (17th October 2014) - Asano, Michiko; Taki, Yasuyuki; Hashizume, Hiroshi; Takeuchi, Hikaru; Thyreau, Benjamin; Sassa, Yuko; Asano, Kohei; Kawashima, Ryuta
Abstract Introduction Like sleeping and eating habits, the study habits adopted by children when they are at home are important contributors to lifestyle and they affect cognitive ability. It has recently been reported that sleeping and eating habits change the brain structure of children. However, no research on the effect of study habits at home on the brain structure of children has been conducted thus far. We investigated the effects of study habits at home on the brain structures of healthy children by examining correlations between study time at home and changes in brain structure over the course of 3 years. Methods We used the brain magnetic resonance images of 229 healthy children aged 5.6–18.4 years and computed the changes (time 2–time 1) in regional gray matter and white matter volume (rWMV) using voxel‐based morphometry. Whole‐brain multiple regression analysis revealed a significant positive correlation between study time at home and changes in rWMV in the right superior frontal gyrus (SFG). Behaviorally, we found a significant positive correlation between study time at home and change in the verbal comprehension index (VCI), one of the subscales of the Wechsler Intelligence Scale for Children–third edition (WISC–III). Results and Conclusions Given that the SFG is involved in memory control and that the VCI measures abilities related to vocabulary, our results indicate that greater SFG involvement in the memorization component of longer study times may result in greater increases in the number of axons and more axon branching and myelination, causing plastic changes in the neural network involved in memory processes.